Aspergillus arthritis: analysis of clinical manifestations, diagnosis, and treatment of 31 reported cases. (8th September 2016) - Gamaletsou, Maria N.; Rammaert, Blandine; Bueno, Marimelle A.; Sipsas, Nikolaos V.; Moriyama, Brad; Kontoyiannis, Dimitrios P.; Roilides, Emmanuel; Zeller, Valerie; Taj-Aldeen, Saad J.; Henry, Michael; Petraitis, Vidmantas; Denning, David W.; et al.
Abstract: Aspergillus arthritis is a debilitating form of invasive aspergillosis. Little is known about its epidemiology, clinical manifestations, laboratory features, treatment, and prognosis. Cases of Aspergillus arthritis were reviewed in the English literature from 1967 through 2015 for variables of arthritis with Aspergillus spp. recovered from joint and/or adjacent bone, underlying conditions, symptoms, signs, inflammatory biomarkers, diagnostic imaging, management, and outcome. Among 31 evaluable cases, 87% were males and 13% pediatric. Median age was 50 y (range 1–83 y). Seventeen (55%) patients were immunosuppressed with such conditions as hematological malignancies (26%), corticosteroids (39%), and/or transplantation (26%). Approximately one-half (52%) of patients had hematogenous seeding of the joint, and more than 80% had de novo infection with no prior antifungal therapy. Oligoarticular infection (2–3 joints) occurred in 45% and contiguous osteomyelitis was present in 61%. Clinical manifestations included pain (87%), edema (26%), and limited function (23%), with knees (35%), intervertebral discs (26%), and hips (16%) being most commonly infected. Aspergillus fumigatus constituted 77% of cases followed by Aspergillus flavus in 13%, Aspergillus niger in 3%, and not specified in 7%. Median ESR was 90 mm/hr and median CRP was 3.6 mg/dl. Median synovial fluid WBC was 17, 200/μL (7, 300-128, 000) with 72% PMNs (range 61–92). Osteolysis occurred in 35%, and soft-tissue extension 47%. Nineteen patients (61%) were managed with combined medical and surgical therapy, 10 (32%) with medical therapy only, and 2 (6%) surgery only. Amphotericin B and itraconazole were the most frequently used agents with median duration of therapy of 219 days (range 30–545). Surgical interventions included debridement in 61%, drainage 19%, and amputation 6%. Complete or partial response was achieved in 71% and relapse occurred in 16%. Medical therapy was reinstituted with successful outcome in these patients. Overall survival was 65%. Aspergillus arthritis mainly develops as a de novo infection involving knees and intervertebral disks in immunocompromised patients with localizing symptoms. Contiguous osteomyelitis is frequently observed. Diagnosis is established by synovial fluid culture. Aspergillus arthritis is therapeutically challenging with most patients undergoing surgery and protracted antifungal therapy.